Nāgaraka in the Kāmasūtra: An Introduction to Masculinity in Early India - Singh, Sukhdev (Masculinidades y cambio social, 2021)
The idea of masculinity is malleable in the Kāmasūtra. This study pinpoints the factors that build or refashion masculinity. It hinges on the economic stability or declination, and undergoes changes accordingly. This study suggests that economic declination might create a category of service providers, for instance, the veśyā, sub-Nāgaraka and the tṛtīyā prakṛti, or third nature, person who corroborate malleability and fluidity of masculinity. This study also suggests that idea of masculinity is disturbed when females enter the masculine domain of kāma-related knowledge. Overall, kāma is not exclusively concerned with masculinity.